TECHNICAL THINKING OF PUPILS IN THE CONTEXT OF SPATIAL IMAGINATION - TOMKOVA, Viera (Trends in education, 2014)
The contribution deals with the need for development in the area of spatial awareness in technical education at the lower secondary level of elementary schools. The author made the research in all grades of an elementary school orientated on the spatial awareness and the ability to imaginary manipulate with objects. Based on the assessment of our research the author designs solution for support of development of spatial awareness in technical subjects.
Keywords: technical thinking; space imagination; education of pupils.